Between mages, warriors and archers: female objectification in Dragon’s Crown Pro (Simbiótica. Revista Eletrônica, 2025)
Despite the growing female representation, not only as players but as characters, in video games, this scenario isn’t followed by a good portrayal of women in these productions. Dragon’s Crown Pro, released in 2013 and remastered in 2018, presents six playable characters, equally divided by their genders (three men and three women). However, this alleged equity of genders faces differences when it comes to gender roles. Based on an analysis method studying the aesthetic, narrative and mechanic dimensions of the video games (Araújo, 2021), this study shows that Dragon’s Crown Pro recurs to misogynistic and sexist ideals to conceptualize its characters, reproducing an ideal of femininity that associates characteristics as beauty and frailty to the women in this universe
Keywords: gender; videogames; character; dragon's crown pro